PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KOMITMEN ORGANISASIONAL, BUDAYA ORGANISASI DAN TATA KELOLA TERHADAP KINERJA DOSEN PERGURUAN TINGGI SWASTA DI PROVINSI BANTEN - Naufal Affandi; Yetty Supriyati; Kadir Kadir (Universitas Bina Bangsa, 2021)
This study aims to formulate a model and analyze the direct influence of Transformational Leadership, Organizational Commitment and Organizational Culture on Governance and Lecturer Performance in Private Universities in Banten. This study uses an associative quantitative approach, or research aimed at knowing the effect of exogenous variables on endogenous variables. Data collection using survey methods, and analysis techniques using SEM with Lisrel 8.80 software. The population in this study were lecturers at Bina Bangsa University, Banten Jaya University and Serang Raya University, as many as 211 lecturers participated as respondents in this study. The results showed that (1) Transformational Leadership Has No Significant and Positive Effect on Governance, (2) Transformational Leadership Has No Significant and Negative Effect on Lecturer Performance, (3) Organizational Commitment Has Significant and Negative Effect on Governance, (4) Organizational Commitment Significant and Positive Influence on Lecturer Performance, (5) Organizational Culture Has No Significant and Negative Effect on Governance, (6) Organizational Culture Has No Significant and Negative Effect on Lecturer Performance, (7) Governance Has Positive and Influence on Lecturer Performance. There is empirical evidence and novelty or new findings that the existence of good governance can improve Lecturer Performance, with a positive correlation direction coefficient.